ISOLATION, MOLECULAR CHARACTERIZATION, AND ANTIMICROBIAL RESISTANCE TEST OF UROPATHOGENIC ESCHERICHIA COLI WITH ASSESSMENT OF INTERLEUKIN-10 IN RHEUMATOID ARTHRITIS PATIENTS WITH UTI - ZEINAB JASEM AL-AZZAWI; ASHWAK BASIM AL-HASHIMY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: It was aimed to isolate Escherichia coli bacteria in rheumatoid arthritis (RA) patients with urinary tract infection (UTI), examination of the antimicrobial sensitivity test, molecular detection of 16SrRNA, UidA virulence gene of the pathogens, and assessment of the level of interleukin (IL)-10 in the sera of RA patients. Methods: Two hundred and sixteen (116 RA patients with suspected UTI and 100 healthy controls without RA or UTI) were enrolled, midstream urine samples (MSU) and blood were collected from different ages and both sexes. All isolates were diagnosed based on microscopic examinations and morphological characteristics using suitable media. The diagnosis was confirmed by the Vitek2 system. Molecular identification was carried out by the polymerase chain reaction (PCR) technique. The evaluations of the immune marker were determined through an enzyme-linked immunosorbent assay (ELISA) test, which was the first investigation in Iraqi RA patients. Results: The results showed that E. coli had the highest percentage, representing 25.8%. Molecular methods, such as the PCR technique, were used to identify the E. coli by 16sRNA and UidA virulence genes; therefore, 26 of the isolates (86.66%) were identified through the presence of both genes. Testing antibiotic sensitivity against 13 different antimicrobial agents showed that E. coli isolates were highest resistance with high significant differences (p≤0.01) for rifampicin25 (83%), ampicillin/sulbactam 20 (67%), cefotaxime 19 (63%), trimethoprim/sulfamethoxazole 17 (57%), ciprofloxacin 16 (53%), gentamicin 12 (40%), while there is intermediate resistance to cefotrixone 10 (33%) with non-significant susceptibility rate 20 (67%), (p=0.068). In contrast, the isolates showed high susceptibility to imipenem 29 (79%), meropenem and amikacin 28 (94%), piperacillin/ tazobactam 27 (90%), and tigecycline 26 (87%) respectively, with highly significant differences (p=001). In addition, high significant sensitivity to cefotazdime 21 (70%), (p=0.0001). The current study demonstrated that E. coli possessed a multi-drug resistance against most of used antibiotics. Molecular detection of 26 bacterial isolates containing 16SrRNA and UidA virulence genes using a conventional PCR test. Five milliliters of venous blood sample from each patient under aseptic technique, the blood samples were collected from the same people from whom urine samples were collected for immunological analysis, such as rheumatoid factor, erythrocyte sedimentation rate, C-reactive protein, and anti-CCP, results exhibited positive reaction and clear elevation levels of antibodies in the serum of RA-infected patients. Analysis of IL-10 in patients’ sera, which was separated from 5 mL of venous blood sample for (30 patients with positive bacterial growth cultures of E. coli and 8 healthy controls), and the level was measured using the ELISA technique. The level of IL-10±SE increased non-significantly (p≥0.05) in RA patients with E. coli UTI (con 24.95 pg/mL±2.64 vs. 18.39 pg/mL±2.52), respectively, in comparison to healthy controls. The mean level of IL-10 reached 25.6 pg/mL differs significantly in RA patients’ era with UTI who were infected with E. coli. Conclusion: E. coli is the most predominant multidrug-resistant pathogen responsible for UTIs in RA patients, who had virulence genes to enhance the immune reaction, and IL-10 may have a role in RA risk.